Transplantation of neuron‐inducing grafts embedding positively charged gold nanoparticles for the treatment of spinal cord injury. Issue 3 (18th April 2022) - Ko, Wan‐Kyu; Kim, Seong Jun; Han, Gong Ho; Lee, Daye; Jeong, Dabin; Lee, Sang Jin; Han, In‐Bo; Hong, Je Beom; Sheen, Seung Hun; Sohn, Seil
Abstract: In this study, we aimed to investigate the recovery after traumatic spinal cord injury (SCI) by inducing cellular differentiation of transplanted neural stem cells (NSCs) into neurons. We dissociated NSCs from the spinal cords of Fisher 344 rat embryos. An injectable gel crosslinked with glycol chitosan and oxidized hyaluronate was used as a vehicle for NSC transplantation. The gel graft containing the NSC and positively charged gold nanoparticles (pGNP) was implanted into spinal cord lesions in Sprague–Dawley rats (NSC‐pGNP gel group). Cellular differentiation of grafted NSCs into neurons (stained with β‐tubulin III [also called Tuj1]) was significantly increased in the NSC‐pGNP gel group (*** p < 0.001) compared to those of two control groups (NSC and NSC gel groups) in the SCI conditions. The NSC‐pGNP gel group showed the lowest differentiation into astrocytes (stained with glial fibrillary acidic protein). Regeneration of damaged axons (stained with biotinylated dextran amines) within the lesion was two‐fold higher in the NSC‐pGNP gel group than that in the NSC gel group. The highest locomotor scores were also found in the NSC‐pGNP gel group. These outcomes suggest that neuron‐inducing pGNP gel graft embedding embryonic spinal cord‐derived NSCs can be a useful type of stem cell therapy after SCI.